2023
DOI: 10.1002/adom.202300201
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the Shortest Intermetallic Distance of Half‐Lantern Diplatinum(II) Complexes for Efficient and Stable Deep‐Red Organic Light‐Emitting Diodes

Abstract: A fast radiative decay process for long-wavelength molecular light-emitters is vital to achieving a high emission efficiency by outcompeting the nonradiative decay imposed by the energy-gap law. An ensuing short emission lifetime is also beneficial for fabricating high-performance organic light-emitting diodes. Herein a series of half-lantern dinuclear platinum(II) complexes is reported, which shows high-efficiency deep red phosphorescence (𝝀 em > 660 nm). The molecules are designed to have a cofacially align… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Thus, they could be measured in different solvents (10 −4 M), showing a small negative solvatochromism, which is characteristic of charge transfer transitions (Figure S14 [dσ*(Pt−Pt) → π*(C ∧ N)]. [18][19][20][21][22][23][24][25][26][27][28][29][30]32,33,35,36 Those for metal− metal bond Pt 2 (III,III) derivatives are originated from an admixture of axial ligand (X) to metal−metal charge transfer, ( 1 XMMCT) and 1 MC [dσ−dσ*] transitions 47,61 or from 1 LMMCT [π(S ∧ N) → dσ*(Pt−Pt)] transitions. 44 To help with the UV−vis assignments, DFT and TD-DFT calculations were performed on 1, 2, 1-Cl, and 1-I (see Tables S2, S3 and Figures 4, 5, S15).…”
Section: Synthesis and Characterization Of Newmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, they could be measured in different solvents (10 −4 M), showing a small negative solvatochromism, which is characteristic of charge transfer transitions (Figure S14 [dσ*(Pt−Pt) → π*(C ∧ N)]. [18][19][20][21][22][23][24][25][26][27][28][29][30]32,33,35,36 Those for metal− metal bond Pt 2 (III,III) derivatives are originated from an admixture of axial ligand (X) to metal−metal charge transfer, ( 1 XMMCT) and 1 MC [dσ−dσ*] transitions 47,61 or from 1 LMMCT [π(S ∧ N) → dσ*(Pt−Pt)] transitions. 44 To help with the UV−vis assignments, DFT and TD-DFT calculations were performed on 1, 2, 1-Cl, and 1-I (see Tables S2, S3 and Figures 4, 5, S15).…”
Section: Synthesis and Characterization Of Newmentioning
confidence: 99%
“…In this regard, half-lantern platinum complexes with C ∧ N cyclometalated ligands and strong intermetallic interactions ( d Pt–Pt ≤ 3 Å) are some of the most representative cases of 3 MMLCT [dσ*­(Pt) 2 → π*­(C ∧ N)] emitters. Among them, mercapto- or hydroxy- ,, substituted N-heterocycles have been typically used as 4-bond bridging ligands to prepare compounds with bright red emissions that, in some cases, have been successfully implemented in organic light-emitting diodes. , Recently, α-carboline or 10 H -pyrido­[3,2- b ]­[1,4]­benzoxazine has been used instead so as to push further the emission toward the deep red or NIR spectral region because the use of these rigid bridges confine close Pt···Pt contacts. Besides, comprehensive studies on these and also on related complexes have shown that changes on the chromophoric C ∧ N ligands can push the emission to red as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triplet excitons are generally dark due to the spin-forbidden transition. 6,7 Different technologies have been exploited to harvest triplet excitons, such as phosphorescent, 8–14 thermally activated delayed fluorescence (TADF) 5,15–21 and hybridized local charge transfer (HLCT) emission. 22–27 Unlike closed-shell emitters, mono-radicals possess a single unpaired electron.…”
Section: Introductionmentioning
confidence: 99%
“…32–36 Excimer-forming Pt( ii ) complexes are attracting more and more interest as potential deep-red or NIR emitters for OLEDs. 21,37–45…”
Section: Introductionmentioning
confidence: 99%